IRAK1/4-Targeted Anti-Inflammatory Action of Caffeic Acid - Woo Seok Yang; Deok Jeong; Young-Su Yi; Jae Gwang Park; Hyohyun Seo; Sang Hyun Moh; Sungyoul Hong; Jae Youl Cho (Hindawi Limited, 2013)
Caffeic acid (CA) is a phenolic compound that is frequently present in fruits, grains, and dietary supplements. Although CA has been reported to display various biological activities such as anti-inflammatory, anti-cancer, anti-viral, and anti-oxidative effects, the action mechanism of CA is not yet fully elucidated. In this study, the anti-inflammatory action mechanism of CA was examined in lipopolysaccharide (LPS) treated macrophages (RAW264.7 cells) and HCl/EtOH-induced gastritis. CA was found to diminish nitric oxide (NO) and prostaglandin E2 (PGE2) production in LPS-stimulated RAW264.7 cells. Additionally, mRNA levels of tumor necrosis factor (TNF)-α, cyclooxygenase (COX)-2, and inducible NO synthase (iNOS) were downregulated by CA. CA also strongly suppressed the nuclear translocation of AP-1 family proteins and the related upstream signaling cascade composed of interleukin-1 receptor-associated kinase 1 (IRAK1), IRAK4, TGF-β-activated kinase 1 (TAK1), mitogen-activated protein kinase kinase 4/7 (MKK4/7), and c-Jun N-terminal kinase (JNK). In a direct kinase assay, CA was revealed to directly inhibit IRAK1 and IRAK4. CA also ameliorated HCl/EtOH-induced gastric symptoms via the suppression of JNK, IRAK1, and IRAK4. Therefore, our data strongly suggest that CA acts as an anti-inflammatory drug by directly suppressing IRAK1 and IRAK4.